2001
DOI: 10.1007/s002130100788
|View full text |Cite
|
Sign up to set email alerts
|

Enadoline, a selective kappa opioid agonist: comparison with butorphanol and hydromorphone in humans

Abstract: These results are discussed with respect to the potential use and safety of kappa agonists for clinical indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
161
1
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(173 citation statements)
references
References 24 publications
7
161
1
4
Order By: Relevance
“…In the past, studies on the precise role of KORs in humans were hampered by the lack of selective agonists, although studies with compounds such as cyclazocine and ketocyclazocine suggested that KOR agonists were psychotomimetic (28). More recently, human studies with the highly selective KOR agonist enadoline (42) indicated that KOR activation induced visual distortions, feelings of unreality, and depersonalization. These effects of enadoline are reminiscent of those previously reported for Salvinorin A (2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the past, studies on the precise role of KORs in humans were hampered by the lack of selective agonists, although studies with compounds such as cyclazocine and ketocyclazocine suggested that KOR agonists were psychotomimetic (28). More recently, human studies with the highly selective KOR agonist enadoline (42) indicated that KOR activation induced visual distortions, feelings of unreality, and depersonalization. These effects of enadoline are reminiscent of those previously reported for Salvinorin A (2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…) to both the selective kappa agonist, enadoline (20, 40 80 & 160 μg/70 kg, i.m. ), and to the full mu agonist, hydromorphone (Walsh et al 2001b). In this case, the profile of subjective effects for butorphanol overlapped considerably with hydromorphone (e.g., increased ratings of good effects, liking, nodding, etc.…”
mentioning
confidence: 85%
“…We were initially interested in butorphanol because of its potential kappa activity and the recognized potential of kappa agents for use in the treatment of cocaine dependence (see (Walsh et al 2001b). However, there are numerous unwanted side effects after administration of selective kappa agonists, including diuresis, sweating, sedation, dizziness, visual distortions, feelings of depersonalization, dysphoria, and, at higher doses, psychotomimetic effects (Dershwitz et al 1991;Kumor et al 1986;Walsh et al 2001b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Èõ ôàðìàêîëîãè÷åñêèé ïðîôèëü áûë ñõîäåí ñ òàêî-âûì òèïè÷íûõ àãîíèñòîâ k-ðåöåïòîðîâ, îïèñàííûõ âûøå, ÷òî òàêaeå ïîäòâåðäèëîñü â õîäå êëèíè÷åñêèõ èññëåäîâàíèé [69]. Ýíàäîëèí è PD117302 ïåðâîíà-÷àëüíî ðàçðàáàòûâàëèñü êàê âûñîêîýôôåêòèâíûå àíàëüãåòèêè [70 -72], íåéðîïðîòåêòîðû è àíòèêîí-âóëüñàíòû [73,74].…”
Section: òðàíñ-2-(34-äèõëîðôåíèë)-n-ìåòèë-n-unclassified